A Study of Team Effectiveness in the Police Department for the District of Kangar, Perlis - Nor Azmi, Johari (2004)
Teamwork continues to play an increasing important role in the structure of organizations. Team effectiveness has often been associated with substantial improvement in productivity and effectiveness of an organization. The purpose of this study was to explore and investigate the relationship of team effectiveness with personal characteristics, motivational goals and organizational factors in Ibu Pejabat Polis Daerah Kangar, Perlis. This study also attempted to determine the explanation for the variance in team effectiveness. The sample of this study comprised the general staff of the personnel of Ibu Pejabat Polis Daerah Kangar, Perlis. The findings revealed that team effectiveness is not significantly related to personal characteristics, motivational goals, role conflicts, communication and leadership factors. However, testing each item used to measure the variables, proved that their inclusion were not misjudged given that, most, if not all, they were found to be significant. This finding and the finding of Cronbach's Alpha, a test of reliability, which produced generally strong Alpha's, it is thought that the disappointing correlational and significance tests were totally unexpected and excusable. The findings also revealed that, team effectiveness in the organization was found to be fairly effective. The levels of trust and respect, role responsibility and cohesion or cooperation between and among employees of Ibu Pejabat Polis Daerah Kangar, Perlis, were also fairly effective. Team members' commitment was found to be low. From the findings, it is recommended that the management of Ibu Pejabat Polis Daerah Kangar, Perlis should emphasize on the importance of team effectiveness in achieving Organizational goals. The management should also emphasize on the development and training of employees to enhance job satisfaction hence improves team effectiveness in the organization .